Cross sections and rate constants for OH + H2 reaction on three different potential energy surfaces for ro-vibrationally excited reagents - Bhattacharya, Sayak; Panda, Aditya N.; Meyer, Hans-Dieter (The journal of chemical physics, 2011)
A systematic study of the reagent ro-vibrational excitations in H2 + OH reaction is presented on three different potential energy surfaces using the multiconfiguration time-dependent Hartree method. An exact form of the kinetic energy operator including Coriolis coupling has been used. Coupled channel results on WDSE surface for vibrational excitation of H2 produce very large cross sections in accordance with the previous approximate results. The rate constant obtained for H2(v = 1) at 300 K on the YZCL2 surface shows an excellent agreement with the most recent experimental result. Quantum dynamical results for ro-vibrational excitation of reagents obtained on the WSLFH surface show similar behavior to previous quasiclassical trajectory studies. The integral cross sections obtained for excited reagent rotations exhibit contrasting trends on the three surfaces. The effects are explained considering the different orientations of the transition state structure and the individual surface characteristics.